Physiotherapeutic aspect of returning to sexual activity after childbirth - Wawryków, Agata; Korabiusz, Katarzyna; Stecko, Monika; Torbe, Andrzej (Journal of Education, Health and Sport, 2020)
Returning to sexual intercourse after childbirth is a significant problem for many young parents. The most frequently recommended period of sexual absenteeism is the postpartum period. It is a period of regeneration of the body and return to full physical activity. There are many reasons for not engaging in sexual activity after childbirth. However, this article focuses on somatic causes, such as those that require the help of a urogynecological physiotherapist.